Ammonium Nitrate‐Assisted Low‐Temperature Synthesis of Co, Co2P@CoP Embedded in Biomass‐Derived Carbons as Efficient Electrocatalysts for Hydrogen and Oxygen Evolution Reaction. Issue 25 (1st July 2020) - Lin, Changqing; Kang, Mingzhen; Zheng, Leizhi; Fu, Xiaoqi; Wang, Shuang
Abstract: Electrochemical water splitting into H2 and O2 provides a promising and sustainable strategy for the future production of clean energy. Herein, we report an ammonium nitrate (AN)‐assisted synthetic strategy to prepare Co, Co2 P@CoP nanoparticles embedded in biomass‐derived porous carbons as bifunctional electrodes for water splitting. The use of AN is not only activating biomass to porous carbons, but also reducing the synthetic temperature significantly. The synergistic effects of the Co2 P@CoP heterostructure could lead to a low adsorption energy of hydrogen (ΔGH* ) and conduction band bending, together with the N/S‐codoped porous carbons could provide large specific surface area and desirable electron‐donating feature, contribute to the remarkable performance with overpotentials of 0.129 and 0.212 V for hydrogen evolution reaction (HER) in 0.5 mol L −1 H2 SO4 and 1 mol L −1 KOH, and 0.328 V for oxygen evolution reaction (OER) in 1 mol L −1 KOH, at a current density of 10 mA cm −2 . Moreover, the Co2 P@CoP/PC catalysts enable overall water splitting with a small cell voltage of 1.63 V to achieve 10 mA cm −2 and exhibit long‐term durability over 1000 min. Abstract : An ammonium nitrate (AN)‐assisted synthetic strategy has been reported to low‐temperature synthesis of Co, Co2 P@CoP nanoparticles embedded in biomass‐derived porous carbons as efficient electrocatalysts for hydrogen and oxygen evolution reaction. The as‐prepared bifunctional Co2 P@CoP/PC catalyst enabled stable overall water splitting with a small cell voltage of 1.63 V to achieve 10 mA cm −2 .